Brief Reviews of Computer Linguistics Research Abroad (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Language is a great gift given only to man.  Therefore, the study of linguistic phenomena is fundamentally different from the study of other social phenomena.  All natural and social phenomena have a systematic structure and self-organization.  It has already been recognized that language is also a systematic phenomenon.  The attention of linguists is focused on a number of issues, such as how this system is organized, what types of units are in its structure, the interaction of these units, the structures formed on the basis of these relationships, the general system and its place in the hierarchical structure.  Customization of such a systemized language to the computer saves users time and saves them from the tedious work of searching through many dictionaries.  All the researches, tireless and painstaking researches of scientists serve only one thing, that is, human interests.